Retrospective assessment of behavioral inhibition in infants and toddlers: development of a parent report questionnaire - Gensthaler, Angelika; Möhler, Eva; Resch, Franz; Paulus, F.; Schwenck, C.; Freitag, C. M.; Goth, K. (Child psychiatry & human development, 2013)
A behaviorally inhibited temperament in early childhood has been identified as a potential risk factor for anxiety disorders in children and adolescents. The purpose of our investigation was the development and evaluation of the factor structure, reliability and validity of the first retrospective parent report measure to assess behavioral inhibition in infants and toddlers. Principal Component Analysis of the Retrospective Infant Behavioral Inhibition Scale (RIBI) supported a three factor solution of the core features of BI in two unselected samples. Internal consistency and inter-rater agreement of both parent judgments were >.90 and >.70. Scores of the RIBI were positively correlated with the parent report temperament questionnaire IBQ and a laboratory-based test at age 14 months with the child.